Encyclopedia of ocean sciences - Steele, John H. 1926-; Thorpe, S. A. FRS; Turekian, Karl K. (Gale virtual reference library, 2001)
Brings together the most current, authoritative, and comprehensive information on the science of the oceans. Includes contributions from leading scientists around the world on the physical processes that drive the oceans and the chemical, biological, and geological disciplines.